2013
DOI: 10.1002/aenm.201300647
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Gel Polymer Electrolyte with High Performance Based on Poly(Vinylidene Fluoride) and Polyborate for Lithium Ion Batteries

Abstract: A composite membrane based on electrospun poly(vinylidene fl uoride) (PVDF) and lithium polyvinyl alcohol oxalate borate (LiPVAOB) exhibiting high safety (self-extinguishing) and good mechanical property is prepared. The ionic conductivity of the as-prepared gel polymer electrolyte from this composite membrane saturated with 1 mol L −1 LiPF 6 electrolyte at ambient temperature can be up to 0.26 mS cm −1 , higher than that of the corresponding well-used commercial separator (Celgard 2730), 0.21 mS cm −1 . Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(126 citation statements)
references
References 46 publications
(48 reference statements)
4
120
0
2
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 group (-C-F) of P(VDF-HFP), hydantoin/BT bonds tightly with the polymer host. 46 Thus the BT nanoparticles maintained a homogeneous dispersion in the composites and neglected evidence of defects was observed between both particle-particle and particle-matrix, indicating strong interfacial bonding and excellent compatibility between nanoparticles and the P(VDF-HFP) matrix. The results can be further proved by the high-magnification SEM images of the nanocomposites (see Figure S4 from the Supporting Information).…”
Section: Characterizationmentioning
confidence: 96%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 group (-C-F) of P(VDF-HFP), hydantoin/BT bonds tightly with the polymer host. 46 Thus the BT nanoparticles maintained a homogeneous dispersion in the composites and neglected evidence of defects was observed between both particle-particle and particle-matrix, indicating strong interfacial bonding and excellent compatibility between nanoparticles and the P(VDF-HFP) matrix. The results can be further proved by the high-magnification SEM images of the nanocomposites (see Figure S4 from the Supporting Information).…”
Section: Characterizationmentioning
confidence: 96%
“…288 Then, a Na-ion capacitor assembled with this GPEs provided high specific energy of 168 Wh kg ─1 and stable cycling with 85 % of the specific capacitance maintained after 1200 cycles. 234 Also, a Na-ion battery Sb/Na3V2(PO4)3 with a low-cost GPE based on cross-linked PMMA was demonstrated. The cell exhibited a highly reversible electrochemical reaction and a stable cycle performance, which was attributed to the enhanced interfacial properties of the gel-polymer electrolyte, especially at the evaluated temperature.…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%
“…Replacing the organic electrolytes with gel polymer electrolytes (GPEs) delivers a promising solution to improve safety by avoiding these crucial issues. [233][234][235] There are extensively explored GPEs based on polymer matrices that are capable of immobilizing a large amount of liquid electrolyte. These GPEs offer both the flexibility of the polymer and the high ionic conductivity of the liquid electrolyte, and enable wide electrochemical windows, excellent cycling durability and improved thermal stability.…”
Section: Highly Concentrated Electrolytesmentioning
confidence: 99%
“…For example, various kinds of composite separators were fabricated by mixing functional ingredients with the supporting matrices, such as inorganic nanoparticles (SiO 2 , TiO 2 , Al 2 O 3 , and Sm 2 O 3 , etc.) [26e30], and polyborate [31,32]. It has also been found that the introduction of some functional groups onto the surfaces of polyolefins or non-woven fabrics before coating modification could enhance the compatibility between substrates and support materials and finally to improve the electrolyte uptake [30,33,34].…”
Section: Introductionmentioning
confidence: 99%